Monster stories for under fives - Stimson, Joan; Early, John Paul (Ladybird Loughborough, 1995)
A collection of monster stories written to appeal to the under fives. The stories feature Cyril the monster, who has an unusual bath, jittery Ginger and the monster who is afraid of children. The book is one of a series designed for anytime reading.